2021
DOI: 10.5194/amt-14-2857-2021
|View full text |Cite
|
Sign up to set email alerts
|

Explicit and consistent aerosol correction for visible wavelength satellite cloud and nitrogen dioxide retrievals based on optical properties from a global aerosol analysis

Abstract: Abstract. We discuss an explicit and consistent aerosol correction for cloud and NO2 retrievals that are based on the mixed Lambertian-equivalent reflectivity (MLER) concept. We apply the approach to data from the Ozone Monitoring Instrument (OMI) for a case study over northeastern China. The cloud algorithm reports an effective cloud pressure, also known as cloud optical centroid pressure (OCP), from oxygen dimer (O2−O2) absorption at 477 nm after determining an effective cloud fraction (ECF) at 466 nm. The r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Finally, the tropospheric SCDs are converted to VCDs using calculated air mass factors (AMFs), which are highly sensitive to the observation geometry, cloud parameters, aerosols, surface conditions and the shape of the NO2 vertical distribution. Over polluted areas, errors in the retrieved tropospheric NO2 VCDs are dominated by the uncertainties in AMF calculations (Boersma et al, 2004;Lorente et al, 2016); errors are sensitive to assumptions on aerosol optical effects, surface reflectance, and a priori NO2 vertical profiles (Zhou et al, 2010;Lin et al, 2014;Lin et al, 2015;Vasilkov et al, 2016;Lorente et al, 2018;Liu et al, 2019;Liu et al, 2020;Vasilkov et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the tropospheric SCDs are converted to VCDs using calculated air mass factors (AMFs), which are highly sensitive to the observation geometry, cloud parameters, aerosols, surface conditions and the shape of the NO2 vertical distribution. Over polluted areas, errors in the retrieved tropospheric NO2 VCDs are dominated by the uncertainties in AMF calculations (Boersma et al, 2004;Lorente et al, 2016); errors are sensitive to assumptions on aerosol optical effects, surface reflectance, and a priori NO2 vertical profiles (Zhou et al, 2010;Lin et al, 2014;Lin et al, 2015;Vasilkov et al, 2016;Lorente et al, 2018;Liu et al, 2019;Liu et al, 2020;Vasilkov et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…104 Also, satellite retrievals of NO 2 and HCHO are subject to large uncertainty in cloudy areas, 42,43,45 and future work that explicitly accounts for the aerosol effects in cloud retrieval could help reduce such uncertainty. 42,65 Evaluation of TROPOMI retrievals and GEOS-Chem simulated a priori profiles with airborne measurements from field campaigns (e.g., WE-CAN, FIREX-AQ) and ground-based MAX-DOAS measurements is warranted to better understand and quantify the uncertainties of TROPOMI observations under fire smoke. Future work should conduct a more detailed evaluation of reactive nitrogen partitioning and VOC composition in GEOS-Chem to determine the mechanisms affecting the formation and loss of NO 2 and HCHO downwind of fires.…”
Section: Resultsmentioning
confidence: 99%
“…We use the a priori profiles from GEOS-Chem simulations at 0.25° × 0.3125° resolution, which significantly reduces the resolution-dependent uncertainties in the operational products that use global simulations at 1° resolution, , but improving the spatial resolution of a priori to a resolution of 0.1° or finer could help further resolve the spatial gradients of NO 2 and HCHO within fire plumes. , The fire injection height is assumed to be constant for all fires in GEOS-Chem and HYSPLIT, which is a major source of uncertainty that could lead to errors in simulating the smoke dispersion, especially for extreme fires . Also, satellite retrievals of NO 2 and HCHO are subject to large uncertainty in cloudy areas, ,, and future work that explicitly accounts for the aerosol effects in cloud retrieval could help reduce such uncertainty. , Evaluation of TROPOMI retrievals and GEOS-Chem simulated a priori profiles with airborne measurements from field campaigns (e.g., WE-CAN, FIREX-AQ) and ground-based MAX-DOAS measurements is warranted to better understand and quantify the uncertainties of TROPOMI observations under fire smoke. Future work should conduct a more detailed evaluation of reactive nitrogen partitioning and VOC composition in GEOS-Chem to determine the mechanisms affecting the formation and loss of NO 2 and HCHO downwind of fires.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the west coast, high biases are found in fire-influenced areas but that may be due to OMI retrievals being too low. Most current operational NO2 retrieval algorithms including OMNO2 v4 treat aerosols implicitly (Liu et al, 2020;Vasilkov et al, 2021), resulting in low retrieved NO2 in fire plumes (Griffin et al, 2021). Travis et al (2016) previously found a 30% GEOS-Chem overestimate of the NASA OMI NO2 v2.1 retrieval over the Southeast US in summer, which they attributed to the NEI2011 emissions being too high, but that model bias is largely corrected in our simulation due both to downward revision of NOx emissions in NEI2016 and to 10-40% higher OMI NO2 retrievals in version 4 of OMNO2 relative to previous versions (Lamsal et al, 2021).…”
Section: Geos-chem Modelmentioning
confidence: 99%